DWH24: a new antibody for fluorescence-based cell death analysis - Ryschich, Anna; Dong, Yan; Schäfer, Michael; Ryschich, Eduard; Karakhanova, Svetlana (Methods and applications in fluorescence, 2023)
Antibodies have gained considerable importance in laboratory and clinical settings. Currently, antibodies are extensively employed for the diagnosis and treatment of several human diseases. Herein, using targeted and cell immunisation approaches, we developed and characterised an antibody clone, DWH24. We found that DWH24 is an IgM κ type antibody that enables excellent visualisation and quantification of dead cells using immunofluorescence, fluorescence microscopy, and flow cytometry. This property was proved by the spontaneous cell death of several tumour cell lines and stimulated T cells, as well as after chemo- and photodynamic therapy. Unlike conventional apoptosis and cell death markers, DWH24 binding occurred in a Ca2+- and protein-independent manner and enabled live imaging of cell death progress, as shown using time-lapse microscopy. The binding specificity of DWH24 was analysed using a human proteome microarray, which revealed a complex response profile with very high spot intensities against various proteins, such as tropomyosin variants and FAM131C. Accordingly, DWH24 can be employed as a suitable tool for the cost-effective and universal analysis of cell death using fluorescence imaging and flow cytometry.
Gesehen am 15.12.2023